Swot Strategy For (Business Process) Handling Claim Irregularity In Warehouse - Djabutafuan, Abdul Azis Gani; Hakim, Muhammad Wildanul; Agusinta, Lira; Rizaldy, Wynd (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2023)
Consignee receive cargo from shipper through services from warehouses. Some irregularities are occured during cargo handling in warehouse.  This research’s aim to find the best alternative operational strategy in overcoming either to eliminate or minimize the claim irregularity and improve cargo handling in warehouse. SWOT analysis Methodology was applied to analyze the  Strength, Weaknesses, Opportunity, and Threats . This research use literature review and secondary data of irregularities at PT Aerojasa in 2021. The result shows each score of the highest weight of strength is 0,74, for weakness is 0,58, for Threat is 0,74 while for Opportunity is 0,75. Those result positioned the Aerojasa on  aggressive strategy quadrant at Space Matrix. The average score on IFE Matrix is 4,3 and of EFE Matrix is 4,16 ,those inteesection show the vertical integration Operation or service strategy on Internal External Matrix.